Management of Indonesian Language Learning for Foreign Speakers (BIPA) at Islamic Religious Higher Education Institutions (PTKI) in Indonesia and Thailand - Siti Isnaniah; Islahuddin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This study aims to compare the management of Indonesian language learning for foreign speakers (BIPA) at PTKI (Indonesian Language Education/TBI IAIN Surakarta) and the Indonesian Language Concentration (KBI) Department of Malay Language (JBM), Fatoni University (FTU), Thailand from the aspects of the curriculum, institutions, teaching materials, instructors, students, and methods. This study uses a descriptive-analytic method with a qualitative approach. Sources of data are informants (BIPA instructors; BIPA managers; managers of the Indonesian Language Program; Indonesian Language Concentration, Department of Malay Language, Fatoni University of Thailand, and Thai students). The results of the study show that teaching Indonesian abroad and domestically is successful because it is proven by the increasing pace of Indonesian language study by foreigners abroad. This has not only occurred at the institutional level of the BIPA program, but it has also led to majors, such as the Indonesian Language Concentration at the University of Malay Language Department. Fatoni Thailand. Meanwhile, the number of students in the PTKI Indonesian Language Program is increasing annually, and International students are increasingly interested in studying at the PTKI TBI Program. The increasing development of teaching Indonesian domestically and abroad requires ideal learning management (curriculum, instructors, institutions, students, teaching materials, and methods). TBI IAIN Surakarta and KBI JBM FTU Thailand appeared to successfully manage Indonesian language learning, although there are slight differences between the two. In terms of curriculum, instructors, institutions, students, teaching materials, and methods, learning Indonesian at TBI IAIN Surakarta is more comprehensive and ready. Therefore, intensive coordination between the two is needed because both are Islamic-based PTKIs to support the Indonesian language's internationalization by making Indonesian as the host in their own country and honored guests in other countries. This paper provides a broad view of BIPA learning management in Islamic higher education institutions in Southeast Asia because not many Islamic Higher Education Institutions in Southeast Asia have BIPA. Therefore, further studies are required on the developments (R & D) related to curriculum, instructors, institutions, students, teaching materials, and methods.